Issues related to occupational exposure to isocyanates: 1989 to 2002 - USA. National Institute for Occupational Safety and Health (Cincinnati, 2004)
"The purpose of this HHE summary document is to amass the past 14 years of isocyanate-related HHEs in a concise format for easy reference and examination by NIOSH researchers, customers, and partners. Any individual report or letter of interest can easily be requested. The scope and presentation of the individual HHEs vary based on the requesters’ needs and the project officers’ professional judgment. The document is not meant to be a state-of-the-art review, but instead, it is intended to provide general insight into the types of isocyanate HHE requests received, and HETAB’s response to them. "